A naturalist's guide to Ontario - Judd, William Wallace, 1915-; Speirs, J. Murray (John Murray), 1909-2001 (Published for Federation of Ontario Naturalists by University of Toronto Press, 1964)
The combination of scientific accuracy and up-to-date practical information makes this book valuable to the naturalist.